One health: Concept, scope and relevance - Tripathi, B N; Barbuddhe, S B (Indian Farming, 2023)
Global changes are accelerated by population explosion, industrialization and geopolitical unrest, which harm biodiversity, deteriorate the ecosystems, and drastically increase human, and animal species migration. Infectious as well as non-infectious diseases emerge and re-emerge as a result of these rapid environmental changes. In response, a transdisciplinary approach among human, animal, plant and environmental health, described as One Health (OH), has gained support and visibility because of its capacity to synergistically address these challenges. One Health introduces a concept embedded in the philosophy of ‘co-existence’ in which every other living being (and inanimate objects like air, water and soil) influences the health of the fellow being. In today’s globalized world, no one discipline, or sector of society may have enough knowledge or resources to prevent the emergence or resurgence of threats like disease, deficiency, crisis, hazard, or disaster (DDCHD).